Effects of different times of stretching on flexibility of ballet dancers - Schiessl, Milena (2016)
Introduction: The stretching exercises have been often used in the sporting context, in order to increase flexibility during trainings and activities, to the overall stretching and focusing the postural reeducation. Objectives: To compare the effects of different times of stretching on the ballet dancer’s flexibility. Methods: Twenty ballet dancers were divided into three groups: a control group (CG), that was only evaluated; a 30-second group (30G); and a three-minute group (3G), which were assessed after two repetitions of hamstring stretches and thigh adductions. The assessments were carried out using anthropometric data and indexes of flexibility collected by goniometry and Wells’ sit-and-reach box. Results: The results showed no significant difference between groups in relation to the flexibility evaluation. Conclusion: There was no significant difference between the times of stretching. The data suggest that a shorter stretching time may be used in rehearsals and performances as part of physical preparation by the ballet dancers.